Methodology to Evaluate Dripper Sensitivity to Clogging due to Solid Particles: An Assessment. (23rd October 2018) - Lavanholi, Rogério; Oliveira, Fabricio C.; Camargo, Antonio P. de; Frizzone, José A.; Molle, Bruno; Ait-Mouheb, Nassim; Tomas, Séverine
Abstract : Emitter clogging is a major problem in microirrigation systems, which may result from the isolated or combined effects of physical, chemical, and biological agents. Clogging caused by suspended solid particles is the most common plugging form of emitters. Water quality and emitter geometry are key aspects in clogging processes. Any suitable test procedure to assess the sensitivity of drippers to clogging should take into account the predominant factors that influence clogging and must reproduce the field conditions. This research set out to assess the performance and suitability of a laboratory clogging test procedure in order to validate a methodology and to provide scientific results that may support the standardization of a clogging test method. The evaluated methodology has been used by the IRSTEA laboratory since 1974 (Platform of Research and experiment on Science and Technology for Irrigation - PReSTI, formerly LERMI) and its contents are currently being discussed by the ISO TC23/SC18 committee. The aim is to define a standardized testing protocol to evaluate the sensitivity of emitters to clogging due to solid particles. Replications analyzing the clogging resistance of four models of emitting pipes were carried out in a laboratory. The clogging test procedure enabled an accurate assessment of the combinations of concentration and size of particles that caused clogging in each model of dripper. However, a significant variability in degree of clogging was identified when the results of replications for each model of dripper were compared. Several requirements, concerns, and improvements related to the clogging test protocol were discussed.